Study of Tea Making from Coffee Leaves - Freddy Hotmaruli Tua Siringoringo; Zulkifli Lubis; Rona J. Nainggolan (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Nowdays coffee leave have not a lot been use. With the existence of tannin in the coffee leaves, it is hope that they can be used as a tea with a special characteristic, as a fresher beverage and medicine. This research was conducted on April to June 2012 in laboratory of analytical food chemistry, Faculty of Agriculture, North Sumatera University, Medan, using factorial completely randomised design with two factors i.e : fermentation time (60, 90, 120 and 150 minutes) and drying temperature (80, 85, 90 and 95oC). Parameters analysed were tannin content, water content, and ash content, organoleptic values (taste, colour, particle appearance and infuse leaf colour). The results showed that time of fermentation had a highly significant effect on all  parameters. Temperature of drying had a highly significant effect of tannin content, water content, ash content, taste, colour, infused leaf and had a significant effect on particle appearance. The best interaction of time of fermentation and temperature of drying was  90 minutes and 95oC respectively